2017
DOI: 10.4314/tjpr.v16i4.5
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA and gene signature of severe cutaneous drug hypersensitivity reactions reveal the role of miR-483- 5p/miR-28-5p in inflammation by targeting Granulysin gene

Abstract: Purpose: To build a microRNA and gene signature of severe cutaneous adverse drug reactions (SCAR), including Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…18 Some studies suggest that miRNAs, such as miR-18a-5p, miR-124, miR-214 miR-483-5p and miR-28-5p, play an essential role in regulating gene expression and are associated with keratinocyte apoptosis in SJS/TEN. [19][20][21] A recent study found that overexpression of plasma exosomal miR-375-3p in SJS/TEN patients promoted keratinocyte apoptosis. 22 It is possible that the different outcomes of epidermal cell damage between SJS/TEN and DRESS might be related to differences in exosomal miRNA expression in both syndromes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Some studies suggest that miRNAs, such as miR-18a-5p, miR-124, miR-214 miR-483-5p and miR-28-5p, play an essential role in regulating gene expression and are associated with keratinocyte apoptosis in SJS/TEN. [19][20][21] A recent study found that overexpression of plasma exosomal miR-375-3p in SJS/TEN patients promoted keratinocyte apoptosis. 22 It is possible that the different outcomes of epidermal cell damage between SJS/TEN and DRESS might be related to differences in exosomal miRNA expression in both syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that overexpression of miR‐146a is important for allopurinol tolerance in HLA‐B*58:01 carriers, but how miR‐146a suppresses allopurinol hypersensitivity reaction is still unknown 18 . Some studies suggest that miRNAs, such as miR‐18a‐5p, miR‐124, miR‐214 miR‐483‐5p and miR‐28‐5p, play an essential role in regulating gene expression and are associated with keratinocyte apoptosis in SJS/TEN 19–21 . A recent study found that overexpression of plasma exosomal miR‐375‐3p in SJS/TEN patients promoted keratinocyte apoptosis 22 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, histone modification and DNA methylation are risk factors for systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), multiple sclerosis (MS), and other diseases [5][6][7][8][9]. Recent studies have shown that drug hypersensitivity was closely related to microRNAs (miRNAs) [10,11]. Another investigation described the overexpression of miRNA-18a-5p inhibited the expression of Bcell lymphoma/leukemia-2-like protein 10 (BCL2L10), which is an endogenous protein that inhibits apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Hemorrhoids are anal pad tissue and vascular proliferative disease with symptoms of bleeding, pain, prolapse, and perianal itching. The worldwide prevalence of hemorrhoids is as high as 39 % [1,2]. The initial treatment for hemorrhoids includes dietary control, proper hygiene, and sue of stool softeners for easy defecation.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are non-coding small RNA molecules with total lengths of 19 -23 bases [2]. The miRNAs regulate the expressions of multiple target genes in organisms, thereby affecting various physiological processes, including the proliferation, differentiation, and apoptosis of cells [3].…”
Section: Introductionmentioning
confidence: 99%